Temporal trend of opioid and nonopioid pain medications: results from a national in-home survey, 2001 to 2018 - Yun Wang; Dan Wu; Alexandre Chan; Chih-Hung Chang; Vivian W.Y. Lee; Michael B. Nichol (PAIN Reports, 2022)
Abstract. Introduction:. The opioid epidemic persists in the United States. The use of opioid medications is often assessed by claims data but potentially underestimated. Objectives:. We evaluated the temporal trend in the use of opioid and nonopioid pain medications from a national survey. Methods:. Using data from the 2001 to 2018 National Health and Nutrition Examination Survey (NHANES), we examined the current use of prescription analgesics in the past 30 days among 50,201 respondents aged 20 years or older. Joinpoint regressions were used to test statistically meaningful trends of opioid vs nonopioid analgesics. Results:. The mean percentage of people who had pain medications in the past 30 days was 6.4% (5.3%-7.1%) for opioid and 11.3% (9.0%-14.8%) for nonopioid analgesics. The availability of opioid and nonopioid prescriptions at home has remained stable, except for the slight decline of opioids among cancer-free patients in 2005 to 2018. The most frequently used opioid analgesic medications included hydrocodone/acetaminophen, tramadol, and hydrocodone. Conclusion:. We uniquely measured the proportion of people who had opioid and nonopioid pain medications at home in the United States and supplemented the previous knowledge of prescription rates mainly obtained from claims data.